Pengembangan Aplikasi DVR Driving dengan Fitur Remote Live Streaming dan Speedometer Berbasis Android - Nico Gufron; Justinus Andjarwirawan; Agustinus Noertjahyana (Jurnal Infra, 2021)
On this era, motor vehicles already help people on daily basis, helping people to deliver goods, or transporting people. But on the way, there is a disaster waiting, either accidents on other vehicles or other accidents. Therefore, in this thesis will develop an application for DVR based on Android, equipped with additional features, such as GPS, Speedometer, and Live Streaming. In this application, users are able to record and take pictures with location and description about the videos and photos they take. Furthermore, live streaming feature added to help other users to join live streaming just entering channel name. Live streaming library helped by Agora Video Broadcasting library. The tests were carried out by adding applications to different smartphone devices